RESOURCE-BASED VIEW (RBV) AND VALUE CHAIN BASED INTERNAL CAPABILITY ANALYSIS IN MAINTAINING COMPETITIVE ADVANTAGE IN BANKING SERVICES: A CASE STUDY OF PT BANK CENTRAL ASIA TBK - Aditya Halim Perdana Kusuma; Ackhriansyah Ahmad Gani; Muthia Indah Permatasari; Andi Muh Adib Asharil; Muh. Farhan Firman (Journal Informatic, Education and Management (JIEM), 2026)
The acceleration of financial technology (fintech) and digital banks (neobanks) has created a highly competitive landscape in the national banking industry. This study aims to analyze the internal capabilities of PT Bank Central Asia Tbk. (BCA) in identifying core competencies and mapping value creation to maintain its position as a market leader. The theoretical framework applied is the Resource-Based View (RBV) through the VRIO matrix (Value, Rarity, Inimitability, Organization) and Value Chain Analysis. The research method employs a descriptive qualitative approach with secondary data collection sourced from annual reports, corporate sustainability reports, and related scientific literature. The Value Chain analysis reveals that BCA generates superior value added in operational activities (IT system security) and services (customer service quality and omnichannel ecosystem). Furthermore, the VRIO analysis indicates that its brand equity as a secure transactional bank, massive low-cost funding base (CASA), and adaptive information technology infrastructure are strategic resources that meet the criteria for a sustainable competitive advantage. Conversely, the high investment cost for maintaining the physical network (branch offices and ATMs) is identified as an internal weakness in the digitalization era. This study recommends that BCA accelerate the migration of physical services to cloud-based digital platforms to reduce long-term operational costs.